Test load determination on composite standard Malaysian rubber constant viscosity 60 for earthquake isolator - Salim, Mohd Azli; Md. Saad, Adzni; Sudin, Mohd Nizam; Rosszainily, Intan Raihan Asni; Dmitriev, Andrey N. (Universiti Malaysia Perlis, 2020)
This paper describes the test load determination on composite Standard Malaysia Rubber constant viscosity 60 for earthquake isolators. The usage of natural rubber in the development of earthquake isolators for building application has led to the investigation on its mechanical properties such as hardness, elastic modulus and many more. In this study, the mechanical properties of Standard Malaysian Rubber with constant viscosity 60 with various percentage of carbon black were investigated. The main purpose of this study is to implement the usage of Standard Malaysian Rubber as the main substance in the development of earthquake isolators. The nano-indentation was carried out by using Berkovich tips at a constant load with various holding time and it recorded the highest hardness and elastic modulus values and possessed the lowest penetration depth. This test also revealed that the hardness and penetration depth were independent of the holding time. In contrast, the indentation elastic modulus was found to be highly affected by the holding time. By using the nano-indentation test, it can determined that the mechanical properties of Standard Malaysian Rubber, is more cost-effective, non-destructive, and requires small test piece as compared to the conventional technique.